Method for improving plasticity of amorphous alloy through electrochemical hydrogen charging
Through electrochemical hydrogen charging treatment, the low plasticity and brittleness problems of Zr-based amorphous alloys are solved, which significantly improves its compression plasticity and thermal stability, and has good industrial application prospects.
Patent Information
- Application Number
- CN202411765215.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-25
AI Technical Summary
Zr-based amorphous alloys exhibit low room temperature plasticity and brittle fracture due to lack of grain boundaries and dislocations, limiting their range in practical applications.
Through electrochemical hydrogen charging treatment, an amorphous alloy is used as a cathode and a platinum electrode as an anode, and electrochemical hydrogen charging is performed in the electrolyte to improve the plasticity of the amorphous alloy.
After electrochemical hydrogen charging treatment, the compressive plasticity of the Zr-based amorphous alloy is increased by 5% to 30%, while improving thermal stability without causing crystallization of the sample.
Smart Images

Figure CN119506739A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of amorphous alloy processing, and in particular to a method for improving the plasticity of an amorphous alloy by utilizing electrochemical hydrogen charging. Background Art
[0002] Bulk amorphous alloys have structural characteristics of long-range disorder and short-range order, and therefore have many unique and excellent physical and chemical properties. Among them, Zr-based amorphous alloys have significant application prospects in many fields such as sports equipment and mechanical engineering due to their large critical size, high strength and elastic strain, and relatively low elastic modulus. However, amorphous alloys do not have defects such as grain boundaries and dislocations, and exhibit very low room temperature plasticity, often showing brittle fracture, which severely limits their practical application range. Therefore, it is of great significance to explore an efficient and economical processing method to improve the compression plasticity of Zr-based amorphous alloys, and it has potential application value in the field of hydrogen energy. Summary of the invention
[0003] Based on the above content, the present invention provides a method for improving the plasticity of an amorphous alloy by utilizing electrochemical hydrogen charging.
[0004] To achieve the above object, the present invention provides the following solutions: One of the technical solutions of the present invention is a method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation, wherein an amorphous alloy is used as a cathode connected to a negative electrode of a power supply, and a platinum electrode is used as an anode connected to a positive electrode of a power supply for electrochemical hydrogenation treatment to improve the plasticity of the amorphous alloy.
[0005] The present invention discloses a method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation. The present invention mainly solves the technical problem that the extremely localized shear band of the existing bulk amorphous alloy rapidly expands, leading to material failure and fracture. After electrochemical hydrogenation, the amorphous alloy remains in an amorphous state and its thermal stability and plasticity are improved. After treatment, the compression plasticity of the amorphous alloy sample is increased by 5% to 30%. The present invention utilizes an electrochemical hydrogenation method to treat an amorphous alloy, which has many advantages such as a simple and fast processing method, easy implementation, and strong practicality. It can well overcome the brittleness problem faced by large-scale industrial applications of amorphous alloys, has a large industrial application prospect, and has potential application value in the field of hydrogen energy.
[0006] The present invention discloses the following technical effects: The method of the invention has simple process and low cost, and the compression plasticity of the treated Zr-based amorphous alloy sample is improved by 5 to 9 times.
[0007] The method of the invention can improve the thermal stability of the Zr-based amorphous alloy without causing crystallization of the sample. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0009] Figure 1 XRD patterns of amorphous alloys at different hydrogen charging current densities (a) and hydrogen charging times (b); Figure 2 DSC graphs of amorphous alloys at different hydrogen charging current densities (a) and hydrogen charging times (b); Figure 3 The stress-strain compression curves of amorphous alloys at different hydrogen charging current densities (a) and hydrogen charging times (b); Figure 4 This is a schematic diagram of a device for electrochemical hydrogen charging treatment according to the present invention. DETAILED DESCRIPTION
[0010] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0011] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0012] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0013] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0014] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0015] The present invention relates to a processing method for improving the plasticity of a Zr-based amorphous alloy by adding H element. In an electrolyte at a certain temperature (the temperature interval of electrochemical hydrogenation treatment is regulated by regulating the temperature of the electrolyte), the Zr-based bulk amorphous alloy is subjected to electrochemical hydrogenation treatment at different current densities and times, and microalloying is produced due to the absorption of different contents of hydrogen (10ppm ~ 200 ppm). The addition of hydrogen leads to the generation of additional free volume, and the sample structure softens after hydrogenation, the hardness decreases, and the plasticity increases. This method enhances the forming ability of the Zr-based bulk amorphous alloy, and at the same time has high strength, high toughness, is easy to produce, and can be widely used, so it will have good application prospects and is of great value in promoting the application of high-performance Zr-based amorphous alloy materials in extreme environments.
[0016] The first aspect of the present invention provides a method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation, wherein an amorphous alloy is used as a cathode connected to a negative electrode of a power source, and a platinum electrode is used as an anode connected to a positive electrode of a power source for electrochemical hydrogenation treatment to improve the plasticity of the amorphous alloy.
[0017] In a preferred embodiment of the present invention, the amorphous alloy is a Zr-based amorphous alloy.
[0018] In a preferred embodiment of the present invention, the chemical formula of the Zr-based amorphous alloy is Zr 61 Cu 25 Ti2Al 12 .
[0019] In a preferred embodiment of the present invention, the method for preparing the Zr-based amorphous alloy comprises the following steps: Weighing single-element raw materials according to the composition of the Zr-based amorphous alloy, mixing and smelting, and obtaining an alloy ingot; The alloy ingot is heated to a molten state to obtain a molten metal, and then formed into a shape to obtain the Zr-based amorphous alloy.
[0020] In a preferred embodiment of the present invention, the molding method is to use vacuum pressure difference to suck the molten metal into the mold.
[0021] In a preferred embodiment of the present invention, the diameter of the prepared Zr-based amorphous alloy sample is 2 to 5 mm; the suction casting pressure difference is 0.016 to 0.05 MPa, the overheating power is 8 to 11 kW, and the suction casting power is 5.0 to 10.0 kW.
[0022] In a preferred embodiment of the present invention, the electrochemical hydrogen charging treatment adopts a steady-current mode; the current density of the electrochemical hydrogen charging treatment is 5 - 120 mA / cm 2 .
[0023] In a preferred embodiment of the present invention, the current density of the electrochemical hydrogen charging treatment is 20-80 mA / cm 2 .
[0024] In a preferred embodiment of the present invention, the electrochemical hydrogen charging treatment is performed for 1-24 h.
[0025] In a preferred embodiment of the present invention, the electrochemical hydrogen charging treatment is performed for 2-12 h.
[0026] In a preferred embodiment of the present invention, the components of the electrolyte used in the electrochemical hydrogen charging treatment include H2SO4 and thiourea; the concentration of H2SO4 in the electrolyte is 0.2~1 mol / L, and the concentration of thiourea is 0.01~0.05 mol / L; the solvent of the electrolyte is water.
[0027] In a preferred embodiment of the present invention, the temperature range of the electrochemical hydrogen charging treatment is 10 ~ 50 °C.
[0028] In some embodiments of the present invention, the compression performance of the Zr-based amorphous alloy sample treated by the method of the present invention is tested, and the compression speed is selected to be 1.0×10 -4 s -1 to 5.0×10 -3 s -1 .
[0029] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0030] The electrolyte used in the embodiment of the present invention comprises: 0.5 mol / L H2SO4 solution and 0.03 mol / L H2NCSNH2 (thiourea).
[0031] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0032] The schematic diagram of the device for electrochemical hydrogen charging treatment of the present invention is as follows Figure 4 shown.
[0033] Example 1: Zr 61 Cu 25 Ti2Al 12(The numbers in the subscript represent atomic percentage) Electrochemical hydrogen charging of amorphous alloys at different current densities According to the chemical formula of the Zr-based amorphous alloy, the corresponding high-purity single element raw materials are weighed with an accuracy of about ±0.003 g. The weighed single element raw materials are mixed and placed in a vacuum arc melting furnace for 4 smeltings (3 to 5 smeltings are possible), and Zr with uniform composition is obtained after cooling. 61 Cu 25 Ti2Al 12 Alloy ingot; Under argon conditions, the alloy ingot was heated to a molten state in a vacuum water-cooled copper crucible magnetic suspension induction melting furnace (10.0 kW). The molten metal was sucked into the amorphous alloy rod mold cavity by using a vacuum pressure difference (0.04 MPa). After cooling, the copper mold was opened to obtain a 3 mm rod sample. Subsequently, a diamond cutter was used to cut the rod sample with a height-to-diameter ratio of 2:1 into a 3 mm diameter and 6 mm height rod sample. The two ends of the rod sample were polished with 800#, 1000#, 2000#, and 3000# sandpaper, respectively, and the surface was cleaned and dried with alcohol. The sample was fixed on the copper strip with conductive tape, and the sample was fixed with silicone at the bottom, leaving the side and end of the cylindrical sample as the working area to obtain the test sample; the test sample and the platinum electrode were connected to the negative and positive electrodes of the external power supply as the cathode and anode, respectively, and then the external power supply was adjusted to the steady current mode, and the current density was set to 20 mA / cm 2 , 40 mA / cm 2 , 60 mA / cm 2 , 80 mA / cm 2 , the hydrogen charging time was 2 h, the electrolyte temperature was 30 ℃, and the samples were electrochemically charged with hydrogen; after the hydrogen charging was completed, the samples were taken out.
[0034] Example 2: Zr 61 Cu 25 Ti2Al 12 Electrochemical hydrogenation of amorphous alloys at different hydrogenation times According to the chemical formula of the Zr-based amorphous alloy, the corresponding single element raw materials are weighed with an accuracy of about ±0.003 g. The weighed single element raw materials are mixed and placed in a vacuum arc melting furnace for 4 smeltings (3 to 5 smeltings are possible), and Zr with uniform composition is obtained after cooling. 61 Cu 25 Ti2Al 12Alloy ingot; Under argon conditions, the alloy ingot was heated to a molten state in a vacuum water-cooled copper crucible magnetic suspension induction melting furnace (10.0 kW). The molten metal was sucked into the amorphous alloy rod mold cavity by using a vacuum pressure difference (0.04 MPa). After cooling, the copper mold was opened to obtain a 3 mm rod sample. Subsequently, a diamond cutter was used to cut the rod sample with a height-to-diameter ratio of 2:1 into a 3 mm diameter and 6 mm height. The two ends were polished with 800#, 1000#, 2000#, and 3000# sandpaper, respectively. The surface was cleaned and dried with alcohol, and the sample was fixed on the copper strip with conductive tape. The sample was fixed with silicone at the bottom, leaving the side and end of the cylindrical sample as the working area. The test sample and the platinum electrode were connected to the negative and positive electrodes of the external power supply as cathode and anode, respectively. Then the external power supply was adjusted to the steady current mode, and the hydrogen charging time was set to 2 h, 4 h, 8 h, and 12 h, and the hydrogen charging current density was 20 mA / cm 2 , the electrolyte temperature is 30℃, and the samples are electrochemically charged with hydrogen; after the hydrogen charging is completed, the samples are taken out.
[0035] The hydrogen content was determined by using a Concentrated ONH5000 oxygen, nitrogen and hydrogen analyzer with an analysis accuracy of ±2 ppm. The sample used for hydrogen content determination was a bulk amorphous alloy with a size of φ3×6 mm. After the hydrogen-filled sample was cleaned and dried by ultrasonic wave, the actual hydrogen content was determined. The measured hydrogen content is shown in Table 1.
[0036] Table 1 Measured hydrogen content , The hydrogen-filled amorphous alloy samples were subjected to XRD diffraction analysis on a D8 ADVANCE X-ray diffractometer, with the scanning test angle set to 20°~80°, the scanning speed set to 4° / min, and the step length set to 0.02°. Figure 1 (As cast in the figure indicates the sample that has not been electrochemically hydrogenated) It can be seen from the XRD spectrum of the amorphous alloy sample that the sample after hydrogenation is still amorphous, and with the increase of hydrogen content, the diffraction angle corresponding to the scattering peak gradually moves to a lower angle, causing the structure and volume of the amorphous alloy to expand and the structure to become more disordered.
[0037] The thermophysical properties of the hydrogen-filled amorphous alloy samples were analyzed in a synchronous thermal analyzer TG-DSC (PerkinElmer STA 6000) with a heating rate of 20 K / min, a temperature range of 30 ~ 1200 °C, and an argon atmosphere. Figure 2 As shown, the glass transition temperature was found T g It increases with the increase of hydrogen content, and the presence of hydrogen also increases the crystallization temperature Tx , the supercooled liquid phase region becomes wider, thereby improving the thermal stability of the amorphous alloy.
[0038] The YTP400-4E05A high and low temperature mechanical properties test system was used to carry out room temperature compression tests on hydrogen-filled samples at a strain rate of 1.0×10 -4 s -1 To ensure the accuracy of the experiment, the prepared amorphous sample was smoothed with sandpaper to make its two ends parallel to ensure that the sample was subjected to uniform force during the compression process, thereby reducing the error. The stress-strain curve is shown in Figure 3 It is found that hydrogen will redistribute the free volume in the amorphous alloy, which in turn leads to the rearrangement of the atomic structure. Adding a small amount of hydrogen significantly enhances the inhomogeneity of the structure, and the plasticity of the amorphous alloy increases from the original 3% to 30%, significantly improving the compression plasticity of the amorphous alloy.
[0039] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation, characterized in that: The amorphous alloy is used as a cathode connected to the negative electrode of a power source, and the platinum electrode is used as an anode connected to the positive electrode of a power source for electrochemical hydrogen charging treatment to improve the plasticity of the amorphous alloy.
2. The method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation according to claim 1, characterized in that: The amorphous alloy is a Zr-based amorphous alloy.
3. The method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation according to claim 2, characterized in that: The chemical formula of the Zr-based amorphous alloy is Zr 61 Cu 25 Ti2Al 12 .
4. The method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation according to claim 2 or 3, characterized in that: The preparation method of the Zr-based amorphous alloy comprises the following steps: According to the chemical formula of the Zr-based amorphous alloy, corresponding single element raw materials are weighed, mixed and smelted to obtain an alloy ingot; The alloy ingot is heated to a molten state to obtain a molten metal, and then formed into a shape to obtain the Zr-based amorphous alloy.
5. The method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation according to claim 4, characterized in that: The molding method is to use vacuum pressure difference to suck the molten metal into the mold.
6. The method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation according to claim 1, characterized in that: The electrochemical hydrogen charging process adopts a steady flow mode.
7. The method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation according to claim 1, characterized in that: The current density of the electrochemical hydrogen charging treatment is 5-120 mA / cm 2 .
8. The method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation according to claim 1, characterized in that: The time of the electrochemical hydrogen charging treatment is 1-24 h.
9. The method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation according to claim 1, characterized in that: The components of the electrolyte used in the electrochemical hydrogen charging treatment include H2SO4 and thiourea; the concentration of H2SO4 in the electrolyte is 0.2 ~ 1 mol / L, and the concentration of thiourea is 0.01 ~ 0.05 mol / L; the solvent of the electrolyte is water.
10. The method for improving the plasticity of an amorphous alloy by electrochemical hydrogenation according to claim 9, characterized in that: The temperature range of the electrochemical hydrogen charging treatment is 10 ~ 50 °C.